Korelasi Pendidikan dan Konseling KB Saat Hamil dengan Penggunaan KB Pasca Salin Pada Ibu Nifas di Puskesmas Paringin Selatan - Ruhanah, Ruhanah; Lathifah, Nur; Hateriah, St. (Pusat Riset dan Inovasi Nasional, 2024)
The return of fertility in the mother after delivery is unpredictable. Therefore a woman should start contraception as early as possible after delivery. The low coverage of postpartum family planning at the South Paringin Health Center in 2021 (57.91%) may be due to the low education and not optimal quality of counselling. This study aims to examine the correlation between family planning education and counselling with the use of postpartum family planning. This study used a quantitative method with a cross-sectional approach. With the population of all postpartum mothers in a working area of South Paringin Health Center, from January to October 2022 using a simple random sampling technique of 136 people using the Chi-Square statistical test. The result of this study found that out of 136 people, 87 respondents (63%) used postnatal family planning. The secondary education level was 60 people (44.12%), and 117 people (86.03%) were given family planning counselling. The results of research on the relationship between education and the use of postpartum family planning obtained ρ = 0.430 (ρ > 0.05) and family planning counselling, ρ = 0.032 (ρ <0.05). Concluded that there is no relationship between education and postpartum family planning and there is a relationship between family planning counselling and postpartum family planning.